VALIDITAS ELEKTRONIK KONTRAK SYARIAH PADA FINANCIAL TECHNOLOGY PT. DANA SYARIAH INDONESIA SEBAGAI ALAT BUKTI AUTENTIK - Riska Wijayanti; Dewi Manda Angraini (IAIN Syekh Nurjati Cirebon, 2023)
AbstractA contract is always growing. Shalihun li kulli al-zaman wa al-makan its mean everything can develop according to the era and the masses, but the development of electronic contracts without meeting and seeing the person or object whether it meets the terms of the validity of the contract, while the easier it is to make contracts does not facilitate the emergence of many potential legal problems. The research problem is How is the validity of electronic contracts on fintech of the Indonesian Sharia Fund? Can electronic contracts executed virtually be used as authentic evidence? This research is normative legal research that uses primary and secondary data sources. The data obtained are processed using qualitative descriptive methods. The results of the study prove that based on the jhumur ulama electronic sharia contract can be said to be valid if it meets the conditions for the validity of the contract, namely; shigat, Al 'aqidan, ma'qud 'alaih, and maudhu' al 'aqd. While related to its function as an authentic evidence tool when it meets the formal and material requirements, its existence cannot stand alone and still requires other evidence.Keywords: Electronic Contract, Sharia Contract; Authentic Evidence Tools, Fintech.